AGRICULTURAL RISK MANAGEMENT STRATEGIES: ELIMINATING UNCERTAINTY AND RISKS IN FARMING (Marketing Journal, 2025)
The article analyzes effective strategies for managing risks in agriculture, particularly in the field of farming. The agricultural sector, especially the farming industry, faces specific uncertainties and risks, making risk management both complex and cru cial. This article examines risk identification, risk assessment, and strategic approaches aimed at reducing risks in the farming sector. The paper also explores how to tackle risks associated with climate change, market conditions, and political factors in farming. Key strategies for managing risks include diversification, modernization of irrigation systems, development of insurance systems, and the introduction of advanced agricultural technologies. This article helps in understanding the essential appro aches needed to ensure successful management in agriculture.
Keywords: agriculture; risk management; farming; uncertainty; risk; diversification; insurance; climate change; risk reduction; agricultural technologies